2010
DOI: 10.1002/crat.201000359
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of growth kinetics of bulk III‐V crystals grown by liquid phase electroepitaxy

Abstract: Results of time-dependent simulations of growth of bulk binary III−V crystals by current controlled liquid phase electroepitaxy (LPEE) are presented using GaAs as example. Without any electrical current the LPEE system is isothermal, kept at 1073 K, thus no growth occurs. The electric current density of 10 A/cm 2 leads to ohmic heating of the entire system, Peltier cooling of the Ga-GaAs(seed) interface and electromigration of As species in liquid Ga. Neither Peltier nor Joule effects are considered at the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The hypothesis was checked by one-dimensional simple estimations of mass and heat transport. , The above analysis was oversimplified to obtain insight into real experimental conditions, in particular, the presence of convection and the real geometry of the growth system. Subsequently, the state of the art of stationary and time-dependent simulation using the real growth geometry confirmed that growth is slowed down and stalled by Ohmic heating in the solid. In the following we present the design removing this obstacle and paving the way to efficient growth of large-size high-quality single crystals by LPEE.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The hypothesis was checked by one-dimensional simple estimations of mass and heat transport. , The above analysis was oversimplified to obtain insight into real experimental conditions, in particular, the presence of convection and the real geometry of the growth system. Subsequently, the state of the art of stationary and time-dependent simulation using the real growth geometry confirmed that growth is slowed down and stalled by Ohmic heating in the solid. In the following we present the design removing this obstacle and paving the way to efficient growth of large-size high-quality single crystals by LPEE.…”
Section: Introductionmentioning
confidence: 91%
“…11,12 The above analysis was oversimplified to obtain insight into real experimental conditions, in particular, the presence of convection and the real geometry of the growth system. Subsequently, the state of the art of stationary 13 and time-dependent simulation 14 ABSTRACT: A new liquid-phase technique allowing one to grow large-size single crystals in nearly isothermal conditions by application of electric current flow is presented. The technique, denoted as contactless liquid-phase electroepitaxy (CLPEE), removes the most important drawback of standard liquid-phase electroepitaxy (LPEE), i.e., superheating of the growing crystal by Joule heat generation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has examined the time evolution of the LPEE growth of GaAs through numerical simulations; 75 showing the relative contributions of electromigration and Peltier cooling.…”
Section: Two-dimensional Continuum Modelsmentioning
confidence: 99%
“…Our recent results indicate that a new version of LPEE, which we have named contactless liquid phase electroepitaxy (CLPEE), avoids Joule heat release in the solid bulk [10], the principal effect limiting thickness of crystals grown by LPEE method [11][12][13][14][15]. In the proposed design of LPEE apparatus the electric current still being the driving force for crystallization does not flow through the solution/seed interface.…”
Section: Introductionmentioning
confidence: 99%